Faktor dukungan keluarga terhadap kekambuhan orang dengan skizofrenia di rumah sakit jiwa Naimata, Kupang tahun 2022 - Nobrihas, Risty Suryani; Weraman, Pius; Manurung, Imelda F.E; Sanam, Maxs U.E; Roga, Anderias Umbu (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Schizophrenia is a serious mental disorder that affects around 24 million people, or 1 in 300 people worldwide. The aim of this research is to analyze emotional support, information support, instrumental support, and assessment/appreciation support for the recurrence of people with schizophrenia at the Naimata Kupang mental hospital in 2022. The type of research used is cross-sectional. Research location at Naimata Kupang mental hospital. The research sample consisted of 60 people, and the sampling technique used was simple random sampling. Data analysis uses multiple regression tests. The results showed that emotional support (p = 0.01), information support (p = 0.022), instrumental support (p = 0.028), and assessment support (p = 0.029) were related to the relapse of people with schizophrenia at Naimata Kupang mental hospital in 2022. The results of the multiple logistic regression test show that the model summary table shows that the Negelkerke R square coefficient is 0.510, meaning that the regression coefficient level of 51% is caused by the variables emotional support, schizophrenia information support, instrumental support, and assessment support, which are some of the factors causing the occurrence. patient recurrence at Naimata Kupang mental hospital. The better the emotional support, informational support, instrumental support, and assessment/appreciation support provided by the family, it will reduce the possibility of recurrence. Conversely, if family support is not good, it increases the possibility of recurrence. Family support is one of the most important things for schizophrenia patients in preventing relapse.